Restorative initiatives: emerging insights from design, implementation and collaboration in five countries - Wailling, Jo; Cameron, Graham; Stolarek, Iwona; Turner, Stephanie; Bleakley, Beelah; O’Connor, Nick; Harwood, Catriona; Power, Michael; Turner, Kathryn; Kooijman, Allison; Oelke, Nelly D.; Gustafson, David; et al. (Frontiers in Health Services, 2025)
IntroductionRestorative systems are human centred and distinguished by an emphasis on relational principles and practices. Emerging evidence indicates that a restorative approach holds promise to mitigate and respond to harm in the complex health environment. Advocates are collaborating with clinicians and institutions to develop restorative responses to adverse events.MethodThis paper shares the insights of an international network who have been collaborating to nurture the development of restorative policy and practice in five countries since 2019 (Aotearoa New Zealand, Australia [New South Wales & Queensland]; Canada [British Columbia], England and the United States [California]). Our work is at varying stages of maturity and incorporates co-designing, implementing, and evaluating restorative responses to adverse events.Results & discussionThe viewpoint provides an overview of the core principles, emerging evidence, and shares our collective reflections about the constraining and enabling factors to development. We recognise that we cannot speak to the breadth of work underway worldwide. Our hope is that by drawing on our experiences, we can offer some thoughts about what a restorative lens offers the future of patient and family involvement in patient safety, whilst providing the opportunity for transparent critique of work to date.